Nikah Kontrak Modus Human Trafficking (Kritik Atas Fiqh Munakahah Mazhab Syi’ah) - Fathonah K. Daud (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract, contract marriage or in fiqh called nikah mutcah is a common thing for Shiahfollowers in Iran. In Indonesia alone, contract marriages also occur in variousregions. The implementation of contract marriages always invited controversy, notonly from the legal side which according to Sunni clerics had been removed, butcontract marriages also invited problems and brought madlarat to the rights of womenand children born after the marriage. For example, in this modern era, the realizationof contract marriages has led to human trafficking. One of the most prominent is in thevillage of Arab Puncak, Bogor, West Java, and the modus of sending female workersabroad which is then traded. This has become a polemic and become a criticism of thefiqh of the Shiah, who still legalize mut'ah marriage. In the practice of marriage whichis limited by a certain time it is actually false (bathil) because it is contrary to Islamicsharia. The principle of marriage is for the sacred purpose of building a family that issakinah, mawaddah wa rahmah and that only happens for permanent marriage (nikahdaim). Keyword: Contract marriage, human trafficking, Shiah jurisprudence